Dispensasi Perkawinan Anak di Pengadilan Agama Indonesia: Kritik terhadap Pertimbangan Hakim Berbasis Pancasila dan Islamic Sociological Jurisprudence Theory - Zakia Lutfiah Khoirun Nisa; Rida Kusuma Devi; Adinda Marsha Dwi Sukma; Ahmad Muhammad Mustain Nasoha (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Child marriage dispensation in Indonesia has shown an increasing trend following the amendment of the minimum marriage age through Law Number 16 of 2019. This phenomenon raises concerns regarding the consistency of judges’ considerations in the Religious Courts, particularly in relation to child protection. This study aims to analyze and critically examine such judicial considerations from the perspective of Pancasila values and the Sociological Jurisprudence approach within the framework of Islamic law. This research employs a normative legal method with statutory, conceptual, and case approaches, utilizing qualitative descriptive-analytical and prescriptive analysis based on library research. The findings reveal that judges’ considerations remain largely casuistic and pragmatic, focusing on factual conditions such as out-of-wedlock pregnancy and social pressure. The implementation of Supreme Court Regulation Number 5 of 2019 has not been optimal, resulting in disparities in judicial decisions and failing to fully reflect the principle of the best interests of the child. From the perspectives of Pancasila and Sociological Jurisprudence, these considerations have not yet fully integrated the values of humanity, social justice, and substantive justice. This study concludes that there is a need to strengthen the integration between legal norms, Pancasila values, and sociological approaches within Islamic law in order to produce judicial decisions that are more consistent, just, and oriented toward child protection.